Hydrochloric Acid Leaching Study of Rare Earth Elements from Moroccan Phosphate - Marouane Amine; Fatima Asafar; Latifa Bilali; Mehdi Nadifiyine (Journal of Chemistry)
As part of the valorization of the Moroccan phosphate rock by extraction of rare earths, different experiments on natural Moroccan phosphate from the Gantour Basin (basin of phosphate in the Youssoufia area) were done in the REMATOP laboratory. The response surface methodology was used to study the effects of the influence of different parameters (acid concentration, solid/liquid ratio, duration of the reaction, stirring speed, and temperature) on the progress of the phosphate rock’s dissolution process to determine the optimal parameters for the extraction of rare earths. The analyses were made at the same time on the mineral matrix and the solutions resulting from the attack of this matrix by different concentrations of hydrochloric acid. The rare earth analyses done by the ICP-MS technique have shown an overall amount of rare earths (ΣREs) of 228.408 ppm with the existence of yttrium as the major element.